Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.4647
|View full text |Cite
|
Sign up to set email alerts
|

AB0802 Effects of dietary magnesium supplementation and intra-articular magnesium sulfate on experimental osteoarthritis and potential molecular mechanisms by mrna and lncrna expression profiles screening

Abstract: BackgroundEpidemiological studies of ours and other groups have reported an inverse association between dietary and serum Mg with knee radiographic osteoarthritis (OA) [1–4].ObjectivesTo investigate the effects of dietary magnesium supplementation and intra-articular MgSO4 on the development of experimental rat osteoarthritis, and explore the underlying potential molecular mechanisms by mRNA and lncRNA expression profiles screening.MethodsRat osteoarthritis model was induced by surgery. Articular cartilage dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Entsprechende Befunde fand man auch für den Zusammenhang zwischen Chondrokalzinose und Magnesiumzufuhr [21] [23]. Im Tierversuch zeigte eine diätetische Magnesium-Supplementierung knorpelschützende Wirkungen [24]. Es ist somit wahrscheinlich, dass ein erhöhter Magnesiumverlust bei Azidose zu Problemen im Bereich der Gelenke beitragen kann und eine gute Magnesiumversorgung Gelenkproblemen vorbeugt.…”
Section: Säureempfindliche Natriumkanäleunclassified
“…Entsprechende Befunde fand man auch für den Zusammenhang zwischen Chondrokalzinose und Magnesiumzufuhr [21] [23]. Im Tierversuch zeigte eine diätetische Magnesium-Supplementierung knorpelschützende Wirkungen [24]. Es ist somit wahrscheinlich, dass ein erhöhter Magnesiumverlust bei Azidose zu Problemen im Bereich der Gelenke beitragen kann und eine gute Magnesiumversorgung Gelenkproblemen vorbeugt.…”
Section: Säureempfindliche Natriumkanäleunclassified
“…There is also a need to investigate the clinical utility of MgSO4 in the treatment of OCD, which is frequently seen in arthroscopic surgery. It has been reported that both dietary and magnesium supplements and intra-articular MgSO4 injection may show cartilage protective effects because of the broad changes in the IncRNA and mRNA profile of chondrocytes(Lei et al, 2017).…”
mentioning
confidence: 99%